(123I)FP-CIT SPECT in suspected dementia with Lewy bodies: a longitudinal case study. Issue 4 (8th April 2013) - Siepel, Françoise J; Rongve, Arvid; Buter, Tirza C; Beyer, Mona K; Ballard, Clive G; Booij, Jan; Aarsland, Dag
Abstract : Objectives: Little is known regarding the 'false-negative' or 'false-positive' striatal dopamine transporter binding on SPECT for the diagnosis of dementia with Lewy bodies (DLB). We explored the clinical course in patients fulfilling the criteria for clinical DLB with a normal ( 123 I)FP-CIT SPECT (ie, SPECT scan negative, clinical features positive (S−CF+)) and patients not fulfilling DLB criteria with an abnormal scan (S+CF−). Design: Longitudinal case study over 2–5 years. Setting: Consecutive referrals of patients with mild dementia to dementia clinics in western Norway. Participants: 50 patients (27 men and 23 women; mean age at baseline of 74 (range 52–88)) with ( 123 I)FP-CIT SPECT images underwent cluster analysis: 20/50 patients allocated to a 'DLB' and 8 to a 'non-DLB' cluster were included. Outcome measures: Scores on standardised clinical rating scales for hallucinations, parkinsonism, fluctuations, rapid eye movement (REM) sleep behaviour disorder and visually rated ( 123 I)FP-CIT SPECT. Results: During the follow-up period, in the S+CF− group (n=7), frequency and severity of DLB symptoms tended to increase, particularly parkinsonism (7/7) and cognitive fluctuations (7/7), while severity of visual hallucinations and REM sleep behaviour disorder remained stable. The S−CF+ (n=3) fulfilled the operationalised criteria for probable DLB both at baseline and at the end of the follow-up. Conclusions: The findings suggest that systematic visual analyses of ( 123 I)FP-CIT SPECT can detect people with DLB prior to the development of the full clinical syndrome. In addition, the study indicates that some patients fulfilling clinical criteria for probable DLB have a normal scan, and further studies are required to characterise these patients better.